Martin Luther and the arts : music, images and drama to promote the Reformation - Löwe, J. Andreas (Studies in medieval and Reformation traditions, 2023)
Luther's theory of music -- Hymns and sacred songs -- Martin Luther's 'Mighty fortress' -- Martin Luther on images -- Teaching the Reformation to read images of hate -- Luther and drama.